Does a pint day affect your childs pay? The effect of prenatal alcohol exposure on adult outcomes - J. Peter Nilsson (Institute for Labour Market Policy Evaluation (IFAU), 2008)
This paper utilizes a Swedish alcohol policy experiment conducted in the late 1960s to identify the impact of prenatal alcohol exposure on educational attainments and labor market outcomes. The experiment started in November 1967 and was prematurely discontinued in July 1968 due to a sharp increase in alcohol consumption in the experimental regions, particularly among youths. Using a difference-in-difference-in-differences strategy we find that around age 30 the cohort in utero during the experiment have substantially reduced educational attainments, lower earnings and higher welfare dependency rates compared to the surrounding cohorts. The results indicate that investments in early-life health may have far reaching effects on economic outcomes later in life.
Keywords: I12; I18; J24; 330; Alcohol policy; infant health; education; earnings; Alkoholkonsum; Gesundheit; Kinder; Bildungsniveau; Einkommen; Alkoholpolitik; Schätzung; Schweden